Prospects of Recognition and Development of Cryptocurrencies in the European Union and the Countries of Europe - Dmitri Andreevich Levi (Управленческое консультирование, 2018)
Contemporary history and nowadays reality of cryptocurrencies such bitcoins is discussed in this article. Author reviews history and modern regulation of cryptocurrencies in the major economies in Europe and beyond. The role of bitcoin and block chain technology is being questioned in the article as author claims this technologies to be something more than a simple IT innovation, but a social hook for further development and political engineering. Author examines current legal regulation and its possible advancement and tries to compare certain results in this field with Russian expertise.